2006
DOI: 10.1242/dev.02644
|View full text |Cite
|
Sign up to set email alerts
|

Jagged 1 is a β-catenin target gene required for ectopic hair follicle formation in adult epidermis

Abstract: The Wnt and Notch signalling pathways regulate hair follicle maintenance,but how they intersect is unknown. We show that Notch signalling is active in the hair follicle pre-cortex, a region of high Wnt activity, where commitment to hair lineages occurs. Deletion of jagged 1 (Jag1) results in inhibition of the hair growth cycle and conversion of hair follicles into cysts of cells undergoing interfollicular epidermal differentiation. Conversely, activation of Notch in adult epidermis triggers expansion of the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
253
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(270 citation statements)
references
References 49 publications
15
253
2
Order By: Relevance
“…The Jagged1 gene, which encodes a Notch ligand, has been reported to be transcriptionally activated by the b-catenin/TCF4 complex, a downstream effector in Wnt signaling (Estrach et al, 2006;Katoh and Katoh, 2006). We confirmed that Jagged1 was also a target of Wnt signaling in colon cells by showing that induction of dominant-negative TCF4 in LS174 T-cells inhibited the expression of Jagged1 (Supplemental Figure 1).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The Jagged1 gene, which encodes a Notch ligand, has been reported to be transcriptionally activated by the b-catenin/TCF4 complex, a downstream effector in Wnt signaling (Estrach et al, 2006;Katoh and Katoh, 2006). We confirmed that Jagged1 was also a target of Wnt signaling in colon cells by showing that induction of dominant-negative TCF4 in LS174 T-cells inhibited the expression of Jagged1 (Supplemental Figure 1).…”
Section: Resultssupporting
confidence: 67%
“…The restricted expression of Jagged1 in the normal intestinal mucosa may result from random asymmetric division of intestinal secretory precursors, as described for another Notch ligand, Delta, in adult Drosophila midgut (Ohlstein and Spradling, 2006). There was not a direct correspondence between b-catenin nuclear translocation in the tumors and Jagged1 expression, despite the fact that data in the literature suggest, and in vitro data reported here demonstrate, that Jagged1 can be regulated by Wnt signaling in colon epithelial cells (Estrach et al, 2006;Katoh and Katoh, 2006), conclusions that were extended by Rodilla et al (2009) while this paper was under review. Moreover, we observed that this heterogeneity in Jagged1 expression extended to tumors in the congenic Apc Min/ þ and Apc 1638N/ þ models, two mouse strains in which elevated Wnt signaling initiates intestinal tumor development.…”
Section: D20 D20mentioning
confidence: 44%
See 1 more Smart Citation
“…Yet, the lack of mesenchymal cells derived from the dermomyotome may account for the lack of hair in the specific area. It is, of course, possible that the increase in ␤-catenin within the epidermis of the remaining body may lead to an increase in hair growth, as has been seen in other studies (Gat et al, 1998;Estrach et al, 2006).…”
Section: Discussionmentioning
confidence: 63%
“…In the absence of Notch signaling, the hair shaft still forms and contains appropriately positioned cells expressing markers for each fate; however, because IRS cells fail to adhere to each other, the follicular architecture cannot be sustained, which leads to the transformation of these aberrant HF into epidermal cysts [92][93][94][95]. Very recently, Demehri and Kopan [96] proposed that Notch acting on bi-potential bulge stem cells, or their uncommitted migratory descendents, plays an inhibitory role in preventing bulge stem cells from differentiating into epidermal cells, thus ensuring the follicular fate.…”
Section: Molecular Control Of Hair Follicle Development and Cyclingmentioning
confidence: 99%